1991
DOI: 10.1111/j.1365-2222.1991.tb00836.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of total serum IgE levels in cord and 9‐month sera of infants

Abstract: To characterize IgE levels at birth and changes in those levels during the first year of life and to identify factors that might influence IgE levels in infancy, we measured IgE levels in 1074 umbilical cord sera and in 697 sera obtained at 9 months of age in a healthy population of infants enrolled at birth into the Children's Respiratory Study in Tucson, Arizona, U.S.A. Serum IgE levels at birth and 9 months were log normally distributed with geometric means of 0.09 and 3.87 IU/ml, respectively. Cord serum I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
42
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 17 publications
7
42
1
Order By: Relevance
“…It is possible that it may be an early marker of allergic sensitisation. FeNO is strongly associated with atopy in children, even in the absence of disease [9], and there is evidence that pre-natal and early life exposure to ETS increases the risk of allergic sensitisation in young children [22,23], although the data are not consistent [24]. Another explanation is that FeNO reflects the acute irritant effects of exposure to ETS in this age group [13].…”
Section: Discussioncontrasting
confidence: 39%
“…It is possible that it may be an early marker of allergic sensitisation. FeNO is strongly associated with atopy in children, even in the absence of disease [9], and there is evidence that pre-natal and early life exposure to ETS increases the risk of allergic sensitisation in young children [22,23], although the data are not consistent [24]. Another explanation is that FeNO reflects the acute irritant effects of exposure to ETS in this age group [13].…”
Section: Discussioncontrasting
confidence: 39%
“…The biological plausibility of this effect is similar to that mentioned for active smoking. Most data in the literature concern foetal or child-adolescent populations exposed to parental smoking and they show controversial results: while some authors did not find an association between IgE levels and passive smoking [17,18], the majority did find such an association [15,16,34]. Therefore, further studies are needed, especially in adults and possibly with confirmation of self-reported passive smoking exposure by objective methods (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Cigarette smoking is related to elevated levels of total serum IgE [1,12,13], but there are controversies about the pathogenetic mechanism [2,14]. Inconsistent results have been reported on the association of total serum IgE with passive smoking [15][16][17][18]. OMENAAS et al [3] and SHIRAKAWA et al [6] reported a positive association between work exposure and total serum IgE.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Studies of cord serum IgE levels were the first to examine the effects of maternal smoking on foetal immunology, but did not produce consistent results. Although a study in 1986 reported that cord serum IgE was increased in newborns if the mother smoked [13], many subsequent studies have not confirmed this [14][15][16]. A comprehensive longitudinal study did not find an effect of ETS on the development of atopy in early life [17].…”
mentioning
confidence: 96%